The Influence of Cultural Responsive Teaching (CRT) on Students' Learning Motivation in the Material of Underhand Passing in Volleyball at SMA N 2 Semarang - Kurniawan, Bagas Indra; Zhannisa, Utvi Hinda; Story, Lukas Waskitho's (Journal of Physical Education Innovation, 2025)
Education is one of the important factors in human life to provide life provisions through various learning processes, including physical education, sports, and health. However, physical activity in children is still relatively low, which is a global problem, one of which is the lack of motivation for children to exercise. For this reason, a study was conducted that applied the Culturally Responsive Teaching (CRT) approach in learning underhand passing in volleyball. This study aims to determine the extent to which this approach can increase students' learning motivation. This study was conducted at SMA N 2 Semarang using the classroom action research (CAR) method, which was carried out in two cycles. The subjects of the study were students in class X-10 at school b. The results of the study showed that in cycle I, students' learning motivation was recorded with an average score of 120.27, and experienced a significant increase in cycle II to 141.92, with a percentage increase of 18%. Based on these findings, it can be concluded that the application of the Culturally Responsive Teaching (CRT) approach in class X-10 SMA N 2 Semarang is effective in increasing students' learning motivation in PJOK subjects. Therefore, the CRT approach can be recommended as an alternative in PJOK learning.